Sápmi and the Return of Beowulf: A Socio-Legal Analysis of the Gállok (Kallak) Case - Björklund Cilli,Janine (2018)
This study aims to analyse how the Swedish media has been framing the Gállok case and the events surrounding it. Moreover, it seeks to understand which meaning is attributed to the concept of Sámi customary law within the Gállok process and decision-makings. This is done through Fairclough’s critical discourse analysis. They study is based on a theoretical framework that has its starting point in the Foucauldian concepts of discourse and power/knowledge, and in the socio-legal theory of legal pluralism. The results of the study reveal that despite the mine project might harm a fundamental practice of custom belonging to Sámi tradition and knowledge, the Sámi viewpoints are repeatedly overlooked or underestimated both within the Swedish media and the analysed statements.
Keywords: Gállok; Kallak; Sámi; indigenous; indigenous rights; self-determination; legal pluralism; customary law; reindeer herding; discourse; power/knowledge; media; Jokkmokk; Länsstyrelsen; County Administrative Board; Samitinget; Sami parliament; extractive industries; mining projects